Pengaruh Pendidikan Kesehatan Tentang Gadget terhadap Pengetahuan Remaja di MTs Darul Arafah Raya - Huwaina Af’idah (STIKES Columbia Asia Medan, 2024)
The devices that people use most often today include computers, tablets, smartphones and smartwatches. The aim of this study was to determine the effect of health education on knowledge in Teenagers. This research method is a quasi experimental pre test and post test. This research was conducted on May 2 2024 at the Darul Arafah Raya Islamic Boarding School Jalan Berdikari.1A Lau Bakeri Village, Sampe Cita, Kec. Kutalimbaru, Deli Serdang Regency. Data collection uses direct questionnaire techniques, namely face to face with respondents. The number of samples obtained in this study was 60 people, targeting junior high school students in grade 8 or with an age range of 13-15 years. The data collection tool used in this research was an observation sheet. The results of this study show that there is a significant difference between the level of knowledge before (pre-test) and after (post-test) education about the Influence of Gadgets on Adolescent Health at MTS Darul Arafah Raya. Conclusion: The results of this study show that significant effects of Health education on knowledge in teenagers at Mts Darul Arafah Raya.